Strength Analysis in Geomechanics - Elsoufiev, Serguey A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The book presents a new approach for the solution of geomechanical problems - it explicitly takes into account deformation and fracture in time, which are neglected in classical methods although these properties create important effects. The method reveals the influence of the form of a structure on its ultimate state. It uses the rheological law which accounts for large strains at a non-linear unsteady creep, an influence of a stress state type, an initial anisotropy and damage. The whole approach takes into account five types of non-linearity (physical as well as geometrical ones) and contains several new ideas. For example, it considers the fracture as a process, the difference between the body and an element of the material which only deforms and fails because it is in the structure, the simplicity of some non-linear computations against the consequent linear ones, the dependence of the maximum small strain in dangerous poins of the body only on the material. Professor Elsoufiev included many new solutions of non-linear geotechnical problems to this second edition. .
Introduction: Main Ideas -- Main Equations in Media Mechanics -- Some Elastic Solutions -- Elastic-Plastic and Ultimate State of Perfect Plastic Bodies -- Ultimate State of Structures at Small Non-Linear Strains -- Ultimate State of Structures at Finite Strains.
Keywords: Mechanics; Mechanics, Applied; Geotechnical engineering; Computational intelligence; Solid Mechanics; Geotechnical Engineering & Applied Earth Sciences; Computational Intelligence; Solid Mechanics